Debridement, Antibiotics, Irrigation, and Retention (DAIR) of the Prosthesis after Hip Hemiarthroplasty Infections. Does it Work?. Issue 8 (August 2015) - Kazimoglu, Cemal; Yalcin, Nadir; Onvural, Burak; Akcay, Serkan; Agus, Haluk
Purpose: Debridement, antibiotic, and implant retention (DAIR) is an attractive treatment modality after hip hemiarthroplasty (HA) infections. Data about the success of the procedure after acute onset infections is lacking. The aim of this study was to analyze the clinical outcome and associated risk factors. Methods: A multicenter, retrospective cohort study was designed, including 39 patients with acute onset prosthetic infection who had undergone debridement and irrigation with prosthesis retention. The primary outcome measure was infection eradication without prosthesis removal. We also analyzed how the success rate was influenced by the length of the interval between implantation of the prosthesis and the beginning of the treatment. Results: The overall success rate was 41%. Sedimentation rate over 60 mm/h and the longer duration (2 weeks) after prosthesis implantation were found as factors negatively influencing the success rate. Conclusions: Our results indicated limited success to DAIR- treated patients with infected HA. The high failure rate of DAIR treatment after 2 weeks from the implantation should be taken into consideration.